Analysis of Restorative Justice in the Criminal Justice System - Abdul Halim; Sri Ismoyo (Enigma in Law, 2023)
Restorative justice is a novel approach to the criminal justice system that focuses on repairing relationships harmed by criminal behavior. This strategy seeks to achieve reconciliation, accountability for perpetrators, and improved social reintegration. Victims play an active role in restorative justice, with the ability to speak about the impact of criminal acts on them and interrogate the perpetrator. Perpetrators are required to admit their conduct, express regret, and work to heal the damage done. Offenders are viewed as individuals who, if given the opportunity and help, can reform and become valuable members of society again. Restorative justice approaches include restorative meetings, which allow for open communication, emotional expression, and the search for shared solutions among the perpetrator, victim, and other associated parties. Restorative justice is a more humane and just alternative to traditional, punishment-focused tactics. Although this strategy is not applicable for all criminal acts, it has been shown to be helpful in addressing particular types of criminal acts, improving victim healing, and minimizing the chance of reoffending.